PERENCANAAN BANGUNAN PENGOLAHAN DI PERUMAHAN PESONA KHAYANGAN MARGONDA DEPOK - Eri Setia Romadhon; Albayyinah Putri (FTSP Universitas Jayabaya, 2019)
Clean water originating from certain water sources usually requires physical, chemical and biological treatment before being distributed to regions. The clean water treatment method most often used is physically and chemically, which consists of intake buildings and water treatment plants. After going through the physical and chemical processes in the treatment building, clean water will be distributed to each house. The first thing to do to plan for a clean water treatment plant is to have a regional layout for the treatment building to be built on and to know what water sources can be used in the area. After that, the plan discharge and available discharge can be found at the water source. Water discharge determines the specifications of pipes and pipe accessories used and can find out the remaining water pressure at each node point. Then it will also be known the height of the tower needed, including the pump power needed for clean water distribution. All of these data will determine the dimensions of the water treatment plant. The results of the planning show that the discharge at the water source is sufficient to be distributed to the Pesona Khayangan housing with Q available = 1106,201 m3 / sec, then Q requirement = 0.00778 m3 / sec..